Effects of processing phases on the quality of massai grass seeds - Melo, Lilian; Martins, Cibele; Silva, Givanildo; Pereira, Francisco Elder; Jeromini, Tatiane (Revista Ciência Agronômica, 2018)
Massai grass is an important tropical forage grass. The harvested seeds upon being received by the company, are found to be contaminated with impurities which are removable by processing machines. This procedure is necessary to produce seeds of a quality level within standards established for commercialization and sowing purposes. The objective of this project was to evaluate the effects of processing phases on the physical and physiological quality of massai grass (Panicum maximum x P. infestum, cv. Massai) seeds for commercialization purposes. Seeds were sampled before processing and after leaving the air and screen machine (upper and intermediary screens and bottom); first gravity table (drift, upper and intermediate spouts); treating machine; and second gravity table (upper, intermediate, and lower spouts). Seeds were evaluated as to water content, physical (purity and 1,000 seeds weight) and physiological quality (germination, first count of germination, seedling vigor classification, accelerated aging, seedling emergence in the field, speed of emergence index, and primary root length, shoot length). Massai grass seeds had their physical and physiological qualities improved when they were processed by an air and screen machine and a gravity table. Seeds from the intermediate discharge spout of the first gravity table, after going through the air and screen machine, are those of with highest physiological potential. The seeds of this species do not need to be processed to fit the germination and purity standards when the national market is the goal.